Spatiotemporal forelimb muscle activation during precise asymmetric stepping in rats - Kacie Hanna; Ezequiel M. Salido; Neha Lal; Kiril Tuntevski; Sergiy Yakovenko (PLoS ONE, 2025)
A sequence of muscle actions generates complex movements such as walking or reaching. However, how these coordinated actions subserve complex movements across animals remains unknown. While the sequences of muscle activity have been documented in limb tasks with large animals, the equivalent comprehensive behavioral description of rodent performance is sparse. To this end, we have trained rats to perform precise foot placement, which allows us to assess skilled limb placement during locomotion. Animals were trained on the pegway task, conFigd to impose symmetric or asymmetric (with overstepping) locomotor stepping at the preferred stride length. We collected electromyography from selected representative forelimb muscles implanted with intramuscular differential electrodes and recorded ground reaction forces from the array of force sensors embedded into walkway pegs. The changes in muscle coordination were analyzed for symmetric and asymmetric stepping. The sequence corresponded to the progression of muscle actions responsible for limb lift, flexion and transport, overground clearance, and preparation for ground contact. The stereotyped spatiotemporal sequence of muscle activity was persistent and consistent across asymmetric tasks. These patterns are similar to those observed in cats during locomotion over obstacles and reaching movements. These findings indicate that a temporal sequence of muscle actions is similar across quadrupeds during locomotor tasks with fine stepping control.